Authorities must reverse closure of SOS Disappeared and uphold civil society’s demands for truth and justice (Amnesty International, 2026)
The forced closure of SOS Disappeared is a devastating blow to the fight for truth, justice and reparations in Algeria. By sealing the offices of the main organization advocating for accountability for enforced disappearances -an ongoing crime under international law- Algerian authorities are once again using them to stifle human rights work.
Algeria